Peripheral microvessel area better predicts the severity of coronary stenosis of acute myocardial infarction patients over pulse wave velocity - Chen Chen; Jing Wang; Tian Tian Huo; Bai Lin Zhu; Xin Jin; Zai Hao Zhao; Mei Hua Lin; Jun Xian Liu; Zhen Yi Guo; Wen Hu Xu; Lan Cui; Xiao Nan He; et al. (Scientific Reports)
Abstract Microvascular obstruction (MVO) is linked with adverse clinical outcome in acute coronary syndrome (ACS) patients, therefore, early prediction of MVO with non-invasive peripheral microcirculation is crucial in facilitating optimal treatment. Current study aims to analyze the significance of opisthenar microvessel area (OMA, measured using optical coherence tomography, OCT) in predicting coronary stenosis (Gensini score, GS) and short-term cardiac recovery of ACS patients and the results were compared to those of arterial stiffness parameters (Pulse Wave Velocity, PWV; Ankle-Brachial Index; ABI). Results showed that cardiac functional parameters (e.g. ejection fraction, EF; fractional shortening, FS) and OMA were higher in normal/low risk (GS 0–≤ 20, n = 69) compared to medium/high risk patients (GS > 20, n = 44, P < 0.0001). Furthermore, OMA, EF or FS was negatively associated with the severity of coronary stenosis (P < 0.0001). In addition, OMA was negatively correlated with heart and liver damage parameters (e.g. creatine kinase, CK; creatine kinase muscle brain, CKmB; lactate dehydrogenase, LDH; hydroxybutyrate dehydrogenase, HDBH; aspartate aminotransferase, AST; alanine aminotransferase, ALT) or with inflammatory markers (neutrophil, neutrophil/lymphocyte ratio, NEU, NEU/LYM (NLR); systemic immune inflammation index, SII and system inflammation response index, SIRI), indicating clinical significance of OMA. Conversely, PWV and ABI were not associated with coronary stenosis or organ damage markers. Receiver Operator Characteristic (ROC) analysis showed high specificity and sensitivity of OMA for coronary stenosis (specificity 0.864 or sensitivity 0.87). In conclusion, OMA shows negative associations with the severity of coronary stenosis and adverse clinical parameters indicate that microcirculation measurement from opisthenar possesses prognostic value for severe ACS patients.